EFFECT OF HUMIC ACID ON THE ADSORPTION OF ZINC AND BORON IN CALCAREOUS SOIL AND GROWTH AND YIELD OF SUNFLOWER - Ouda, Marwan; Naser, Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The study aimed to investigate the effect of adding humic acid on the adsorption of zinc and boron and on sunflower growth and yield. Field experiment was conducted at one of the research fields of the College of Agricultural Engineering Sciences, University of Baghdad, during the spring season of 2022, using sunflower (Helianthus annuus L.), cultivar Shamoos planted in Clay loam soil. The experiment involved three factors using a randomized complete block design (RCBD) with three replicates: humic acid (0 and 50 kg ha¹)and them symbols H0,H1, zinc sulfate (0, 15, and 30 kg ha-¹) them symbols Zn0,Zn1,Zn2, and boron (0, 6, and 12 kg ha-¹) and its symbols B0,B1,B2. Results showed that adding humic acid increased zinc and boron adsorption capacity in the soil. Moreover, humic acid, zinc and boron significantly improved plant height, leaf area, seed yield and water-use efficiency, with the highest water-use efficiency observed in the Zn2 treatment at 1.6642 kg m-³.